EXPLORING APPROACHES TO IMPROVING COMMUNICATION AND ENGAGEMENT OF JOB SEEKERS FROM DIFFERENT CULTURAL CONTEXTS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article examines theoretical and practical aspects of intercultural communication in the process of selecting and involving applicants from various cultural contexts. It analyzes the main barriers and challenges that arise during the interaction of representatives of different cultures, as well as modern effective approaches and methods for overcoming them. Practical cases of leading international and national companies that successfully implement multicultural strategies are presented. recruitment and adaptation of personnel. The results of the study may be useful for HR specialists, recruiters and managers working in multinational companies, as well as researchers in the field of intercultural communications and personnel management.